Retrospective Case Analysis of Transnasal Endoscopic Resection of Benign Orbital Apex Tumors: Some Thoughts on Transnasal Endoscopic Surgery - Cheng Li; Yang Gao; Rongxin Chen; Chao Cheng; Pan Yin; Zhihui Zhang; Yinghao Wang; Yuekun Bao; Huan Ma; Jianbo Shi; Rong Lu (Journal of Ophthalmology)
Purpose. To deeply discuss the patient selection, surgical planning, surgical techniques, and the therapeutic challenge for endoscopic transnasal resection of benign orbital apex tumors (OATs). Methods. We retrospectively analyzed the cases of 18 patients (18 eyes) with orbital apex cavernous hemangioma (OACH) who underwent endoscopic transnasal approach for resection of the tumor in Zhongshan Ophthalmic Center from March 2016 to May 2020. At each follow-up visit, the patients underwent measurement of their best-corrected visual acuity (BCVA), slit-lamp examination, indirect ophthalmoscopy, and visual field testing. Results. There were 18 patients, 7 males and 11 females, with a mean age of 49.9 ± 12.6 years (range: 26 to 70 years). All 18 patients had unilateral tumors. Among the 18 cases, 13 were located in the right orbit and 5 were located in the left orbit. Sixteen patients underwent purely endoscopic transnasal surgery, and the other 2 patients underwent an endoscopic transnasal approach combined with a transcutaneous or transconjunctival surgical approach. Fourteen patients’ OACHs were removed completely, 1 patient’s OACH was partly removed, and 3 patients underwent pure decompression of the optic nerve. Fourteen patients gained improved or stable BCVA after surgery. Three patients showed postoperative vision decline, and 1 patient had no light perception after surgery. Conclusions. Endoscopic surgery is an effective surgical technique for the treatment of benign tumors in the orbital apex. It is necessary to strictly select patients and fully evaluate the benefits and risks of tumor completely or partly removed.